CORRELATION BETWEEN ACADEMIC PERFORMANCE AND OBESITY IN SCHOOL-CHILDREN FROM ANAND DISTRICT (International Journal of Physiotherapy, 2017)
Background: Growing childhood obesity epidemic is concerning the health of future generation in any country. Today’s competitive world is increasing the never ending pressure on children to excel in academic performance to ensure bright future. Hence, it is the need of the hour to understand the correlation between obesity and academic performance for implementation of the policies related to obesity prevention and treatment.Methods: 1034 school children were taken randomly according to inclusion and exclusion criteria, and they were divided into two groups: a) 5-11 years and b) 12-18 years. BMI (BMI), Waist Circumference (WC), the Waist-Height ratio (WHtR) and SSFT (Sum of Skinfold thickness) were taken to measure obesity, and the class teacher evaluated academic performance.Results: The prevalence of obesity when assessed by WC revealed highest values as compared to Waist-Height ratio, IOTF-BMI and SSFT. Spearman correlation between obesity (WC) and academic performance revealed that there was a significant negative moderate correlation in urban boys (r = -0.4, p